Mentalization-Based Group Therapy Intervention for Males with Amphetamine Dependence: A Quasi-Experimental Study - Srijan, Kraiwut; Kongsuwan, Vineekarn; Pummanee, Treenut (Pacific Rim International Journal of Nursing Research, 2024)
Thailand is a country with a high proportion of methamphetamine substance abuse users, and the trend is increasing. Methamphetamine is a highly addictive stimulant affecting the central nervous system. Amphetamine addicts are mostly male. Amphetamine addiction is a serious problem often caused by poor attachment in childhood, leading to stress and anxiety, and therefore requires special therapy. A psychotherapy program using mentalization-based group therapy was undertaken in our quasi-experimental study. Programs like this have met with success in several countries. We aimed to test the effectiveness of mentalization-based group therapy on the sense of coherence and self-care behavior among males undergoing recovery from amphetamine dependence at two substance rehabilitation hospitals in southern Thailand. One hospital was the experimental setting, and the other was the control setting. The participants from the two settings were purposively selected and matched by age. The experimental group (n = 32) received the program, and the control group (n = 32) received only usual care. Instruments used for the data collection were a Demographic Data Form, the Sense of Coherence Scale, and the Self-care Behavior Scale. The data were analyzed using descriptive statistics, Chi-square statistics, paired t-tests, and MANCOVA. Results revealed that after receiving the program, the mean scores in the experimental group’s sense of coherence and self-care behaviors were significantly higher than before the program and those of the control group. Advanced practice nurses with special training can apply this program among males with amphetamine dependence. However, comparing the changes in the sense of coherence and self-care behaviors with a longer follow-up is recommended for further study.